PEMETAAN PENYEBARAN STUNTING DENGAN SISTEM CLUSTERING SATSCAN DI KECAMATAN LARANTUKA KABUPATEN FLORES TIMUR - Boy, Antonius; Rahmawati, Arfita; Tomi Pamungkas, Bella Theo (Jurnal Geografi, 2025)
Stunting is claimed to be an issue in national development, one of the problems being that the grouping of stunting distribution areas in Larantuka District is still done manually. Therefore, one of the data clustering analyses that can be applied is using Cluster analysis and mapping. The purpose of this research is to understand the map of the distribution and clustering of stunting cases using the clustering analysis method with the SaTScan software in the Larantuka District, East Flores Regency, which is beneficial in facilitating related agencies in observing the points of stunting case distribution. This research uses a quantitative descriptive method with the aim of describing and objectively illustrating the distribution of stunting in Larantuka. The data collection methods used in this research are through literature studies related to the issues, direct interviews with the sources, and data collection on the number of stunting sufferers in Larantuka District. The analysis results indicate that 2 locations were detected in the Clustering satscan processing, namely cluster 1 with 42 cases and a P-value of 0.00000000000000001, which falls into the high category, while cluster 2 has 15 cases with a P-value of 0.0000000000000033, which falls into the low category. If the P-value is less than 0.05, it shows strong evidence that these clusters have high significance.